Interaction of serum heat shock proteins’ levels with the severity of venous congestion in patients with acute decompensated heart failure with preserved ejection fraction - Yu. S. Timofeev; A. R. Afaunova; A. A. Ivanova; T. Yu. Vedenikin; O. N. Dzhioeva; V. A. Metelskaya; M. S. Pokrovskaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To analyze the interactions between heat shock proteins (HSPs) (HSP27, HSP70 and cardiovascular HSP — cvHSP) serum levels and acute decompensated heart failure (HF) and signs of venous congestion in patients with preserved ejection fraction (HFpEF).Material and methods. The study included 80 patients with HFpEF aged from 50 to 85 years: 60 with acute decompensated HF and 20 with stable HFpEF. HSP levels were estimated with the enzyme immunoassay method using AssayPro (USA) and Cloud-Clone (PRC/USA) reagent kits with detection on a Multiskan FC photometer.Results. The medians of HSP27, HSP 70 and cvHSP in the acute decompensated HFpEF group were significantly higher than in the stable HFpEF group. In the decompensated HFpEF group with mild congestion, the medians of HSP27 (0,58 ng/ml) and cvHSP (905 pg/ml) were significantly lower than in the group of patients with moderate or severe congestion (1,67 ng/ml and 1028 pg/ml, respectively). The medians of HSP27 and cvHSP in the group with ≥3 B-lines in one lung segment were significantly higher than the medians in the group with <3 B-lines by 3,6 times and 1,2 times, respectively.Conclusion. Higher serum levels of HSP27, HSP70 and cvHSP are associated with the acute decompensated HFpEF. HSP27 and cvHSP levels are positively associated with the severity of congestion assessed by VExUS and B-lines.